2005
DOI: 10.1002/cbic.200500218
|View full text |Cite
|
Sign up to set email alerts
|

Quantum‐Dot Aptamer Beacons for the Detection of Proteins

Abstract: Quantum dots (QDs) offer a number of advantages over standard fluorescent dyes for monitoring biological systems in real time, including greater photostability, larger effective Stokes shifts, longer fluorescent lifetimes, and sharper emission bands than traditional organic fluorophores. In addition, QDs all respond to the same excitation wavelength, but emit at different wavelengths; this should allow for the multiplex detection of different analytes in parallel.Recent work has also demonstrated that QDs can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
212
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(217 citation statements)
references
References 16 publications
1
212
1
3
Order By: Relevance
“…Alternatively, nanoparticle derivatization can be carried out in organic solution (Pathak et al 2001) prior to the coupling to amino-modified DNA oligomers, or the 5 end phosphate group of DNA can be reacted with EDC and imidazole to primary amino groups (Hermanson 2008) present on the particle surface (Skaff & Emrick 2003). Apart from covalent conjugation chemistry, avidin-biotin has also been used as the noncovalent receptor-ligand system for the binding of DNA to nanoparticles, both with biotin-modified DNA (Levy et al 2005) and biotin-modified nanoparticles (Niemeyer et al 1998). …”
Section: (I) Biotin Avidin and Derivativesmentioning
confidence: 99%
“…Alternatively, nanoparticle derivatization can be carried out in organic solution (Pathak et al 2001) prior to the coupling to amino-modified DNA oligomers, or the 5 end phosphate group of DNA can be reacted with EDC and imidazole to primary amino groups (Hermanson 2008) present on the particle surface (Skaff & Emrick 2003). Apart from covalent conjugation chemistry, avidin-biotin has also been used as the noncovalent receptor-ligand system for the binding of DNA to nanoparticles, both with biotin-modified DNA (Levy et al 2005) and biotin-modified nanoparticles (Niemeyer et al 1998). …”
Section: (I) Biotin Avidin and Derivativesmentioning
confidence: 99%
“…(9)(10)(11)(12) A wealth of sensitive aptamer-based biodetection approaches have been reported in which aptamers were labeled with molecules such as redox probes, fluorescent dyes, or nanocrystals to be an integral part of signal transduction. (13)(14)(15)(16)(17)(18)(19)(20)(21) In addition, researchers have recently taken advantage of PCR to amplify DNA aptamers for sensitive detection of protein targets. Le and coworkers describe the isolation of a protein-aptamer complex via capillary electrophoresis, followed by PCR amplification of the bound ssDNA and subsequent visualization and quantification by gel electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…Specific uptake of QD-Apt(Dox) conjugates into target cancer cell through PSMA mediate endocytosis evokes the release of Dox from the QD-Apt(Dox) conjugates, resulting in the recovery of fluorescence from both QD and Dox and the intracellular delivery of Dox inside cancer cells. Levy et al demonstrated an aptamer beacon-based approach for detecting the protein thrombin with QD-based fluorescence readout, in which the detection limit was determined to be 1 μM (Levy et al, 2005). Most recently, Cheng et al Once MUC1 peptide binds to the aptamer strand on the surface of QD, fluorescence intensity successively decreases through FRET effect, showing low detection limit for MUC1 (nanomolar level) and a linear response found in blood serum.…”
Section: Fluorescence Resonance Energy Transfer (Fret) System Using Qdsmentioning
confidence: 99%